Natural Gas Hydrate Prediction and Prevention Methods of City Gate Stations. (14th July 2021) - Zuo, Lili; Zhao, Sirui; Ma, Yaxin; Jiang, Fangmei; Zu, Yue
Abstract : During the process of distributing natural gas to urban users through city gate stations, hydrate is easy to form due to the existence of throttling effect which causes safety risks. To handle this problem, a program to quickly calculate hydrate prediction and prevention methods for city gate stations is developed. The hydrate formation temperature is calculated through the Chen–Guo model, and the Peng–Robinson equation of state combined with the balance criterion is used to analyze the water condensation in the throttling process. The Wilson activity coefficient model is used to calculate the mass fraction in the liquid phase of thermodynamic inhibitors for preventing hydrates. Considering the volatility of inhibitors, the principle of isothermal flash has been utilized to calculate the total injection volume of the inhibitor. Moreover, the effects of commonly used methanol and ethylene glycol inhibitors are discussed. In terms of safety and sustainability, the ethanol inhibitor, which is considered for the first time, exhibited better prevention and control effects under conditions with relatively high temperature and low pressure after throttling. Combined with the actual working conditions of a gate station, methanol has the best inhibitory effect, followed by ethylene glycol. From an economic point of view, the benefits of the gas phase of the inhibitor during the delivery of natural gas are obvious; therefore, the method of methanol injection is recommended for hydrate prevention. If the gas phase benefits of the inhibitor are not considered, the ethylene glycol injection method becomes more economical.